2013
DOI: 10.5888/pcd10.120184
|View full text |Cite
|
Sign up to set email alerts
|

Retailer Adherence to Family Smoking Prevention and Tobacco Control Act, North Carolina, 2011

Abstract: IntroductionThe Family Smoking Prevention and Tobacco Control Act regulates the sales and marketing of tobacco products in the United States; poor adherence by tobacco retailers may reduce the effectiveness of the Act’s provisions. The objectives of this study were 1) to assess whether and to which provisions retailers were adherent and 2) to examine differences in adherence by county, retailer neighborhood, and retailer characteristics.MethodsWe conducted multivariate analysis of tobacco retailers’ adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 20 publications
1
51
1
Order By: Relevance
“…SES variables included education,2835 parental education,24 3641 household income,33 4244 Family Affluence Scale (FAS),2123 25 45 family socioeconomic classification,22 free school meal (FSM) eligibility,25 46 47 income/spending money,26 41 48 and occupation 49. Measures of area deprivation included the Index of Multiple Deprivation/area deprivation,25 5054 Index of Relative Socio-Economic Disadvantage,54 household education and income level at ‘zip’ code level,55 56 percentage of population with a college education, 32 33 55 percentage of youth unemployment, percentage receiving social welfare and attending ‘low-qualifying’ schools, 35 53 percentage below 150% poverty level,32 57 and school census tract data 58…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SES variables included education,2835 parental education,24 3641 household income,33 4244 Family Affluence Scale (FAS),2123 25 45 family socioeconomic classification,22 free school meal (FSM) eligibility,25 46 47 income/spending money,26 41 48 and occupation 49. Measures of area deprivation included the Index of Multiple Deprivation/area deprivation,25 5054 Index of Relative Socio-Economic Disadvantage,54 household education and income level at ‘zip’ code level,55 56 percentage of population with a college education, 32 33 55 percentage of youth unemployment, percentage receiving social welfare and attending ‘low-qualifying’ schools, 35 53 percentage below 150% poverty level,32 57 and school census tract data 58…”
Section: Resultsmentioning
confidence: 99%
“…Four US studies28 31 32 56 examined the equity impact of controls on advertising, promotion and marketing of tobacco. Two studies31 32 had a neutral equity impact and two studies demonstrated a negative equity impact 28 56.…”
Section: Resultsmentioning
confidence: 99%
“…Data from an earlier study 55 showed that, particularly in suburban and rural areas, retailers clustered at exits along interstate highways. Thus we created a dichotomous measure of presence of an interstate highway within a tract.…”
Section: Methodsmentioning
confidence: 94%
“…Although studies have assessed brick-and-mortar retailer compliance with the FSPTCA, [2][3][4] no studies have investigated compliance among Internet cigarette vendors (ICVs). One reason could be the difficulty involved in tracking online vendors.…”
Section: Tobacco Products Sold By Internet Vendors Following Restrictmentioning
confidence: 99%